О системе правовых мер охраны водно-болотных угодий в законодательстве Ресублики Белорусь - Речиц, Е.; Recits, Е. (Східноєвропейський національний університет імені Лесі Українки, 2016)
Водно-болотные угодья рассматриваются как комплексные сложно организованные и многофункциональные экологические системы. Обосновывается необходимость применения экосистемного подхода к правовой охране водно-болотных угодий, опирающегося на систему общих эколого-правовых и специальных правовых мер. Специальные меры правовой охраны водно-болотных угодий имеют экосистемный характер и предлагаются к закреплению в законодательстве Республики Беларусь об охране и использовании вод. Applying the ecosystem approach to the legal protection of all types of the wetlands should be based on a combination of the legal mechanisms for the protection the wetlands of two groups of legal actions: 1) the general environmental law; 2) special rules. General ecological-legal measures of legal protection of wetlands are provided by the Republic's environmental legislation, legislation on protection and using lands, on protection and using water, on the use, conservation and protection of forests, for the protection and using of fauna, about the plants , on using mineral resources, air protection and the other acts of the Republic of Belarus and are intended to provide legal protection of the individual components of the environment, forming the wetlands. Special measures for legal protection of the wetland's have a character of the ecosystem andhave proposed to consolidate the law of the Republic of Belarus on protection and using of water.
About the System of Legal Measures for the Protection the Wetlands in the Legislation of the Republic of Belarus.
Keywords: экологические системы; экосистемный подход; правовая охрана водно-болотных угодий; ecological systems; ekosystem's approach; the legal protection of the wetlands